Platinum group elements as geochemical indicators in the study of oil polygenesis - Irina V. Talovina; Regina K. Ilalova; Ivan A. Babenko (Записки Горного института)
This study examines elements of the platinum group (PGE), primarily platinum and palladium, as geochemical indicators in the investigation of oil polygenesis. It has been found that, like other trace elements such as nickel, vanadium, and cobalt, platinum group elements and gold can occur in oil fields at both background levels and in elevated or even anomalously high concentrations. The objective of this research is to analyze PGE and trace elements as geochemical markers to identify the geological factors, including endogenous processes, responsible for these unusually high concentrations in oil. A comprehensive review of the literature on this subject was conducted, along with new data on the presence of precious metals in oils from Russia and globally. The study explores the geological mechanisms behind elevated PGE concentrations in oils, utilizing atomic absorption spectroscopy with atomization in the HGA-500 graphite furnace to measure PGE content. Previously, the tellurium co-deposition method (ISO 10478:1994) was used to isolate noble metals from associated elements. Possible geological origins of abnormally high concentrations of platinum metals in oils have been identified. These include endogenous factors such as the spatial proximity of oil fields to ultrabasic rock massifs, the effects of contact-metasomatic processes, and influences from mantle dynamics. Moreover, data concerning mantle elements can serve as indicators of the depth origins of certain hydrocarbon fluids, thus contributing to the study of oil polygenesis.